The Tradition of Jaran Gading of Ngusaba Dalem in Adat Lebu Village - I Wayan Gama (Pusat Publikasi Nusantara, 2025)
Lack of understanding of the implementation of the Jaran Gading Tradition in Ngusaba Dalem in Lebu Traditional Village, Sidemen District, Karangasem Regency. So it requires scientific academic study. This study aims to (1) describe the means of ceremonies of the Jaran Gading Tradition in Ngusaba Dalem. (2) to describe the procession of the Jaran Gading Tradition in Ngusaba Dalem. (3) to describe the purpose of the Jaran Gading Tradition in Ngusaba Dalem. Tradition is a habit that is born in a certain area and has been passed down from generation to generation and has been carried out for a long time and then passed on to the next generation. Jaran Gading is a yellow/golden horse, while Ngusaba Dalem is an offering ceremony to Ida Bhatara Shiva as an expression of gratitude for all the graces He has given at Dalem Temple. This research is classified as qualitative research with data collection techniques through observation, interviews and document recording. Data analysis using qualitative descriptive analysis consists of data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that (1) The ceremonial facilities used in the ceremony consist of the clothes used and the ceremonial facilities, namely in the form of banten which is presented to each palinggih. (2) The implementation process can be divided into 3 (three), namely: 1) preparation, which is the first activity before carrying out peak activities; 2) the core/peak procession of the event is the core event of the implementation of the activity; and 3) the closing is the last series of events that marks the end of the activity. (3) The purpose is to be a means of offering, a means of supplication, a means of expressing gratitude, a means of fostering a sense of brotherhood. Through this activity, it is hoped that Ida Bhatara Shiva, who is stationed at Dalem Temple , will be pleased to revive this universe and its contents, so that it can be beneficial for human life, and existing creatures, including humans, are given welfare and live well in carrying out their obligations.